Event-triggered semi-global output consensus of discrete-time multi-agent systems with input saturation and external disturbances - Xu, Chengjie; Zeng, Wang; Liu, Chen; Yan, Huaicheng (IEEE transactions on circuits and systems. II, Express briefs, 2023)
In this brief, the event-triggered semi-global output consensus is investigated for discrete-time multi-agent systems subject to input saturation and external disturbances. Under the assumption that the dynamics of all nodes are identical, based on output regulation, a protocol view is proposed by using relative state information. On the basis of Lyapunov stability theory, sufficient conditions for output consensus are obtained. Finally, a simulation result is given to illustrate the theoretical findings.